A perspective on the current state of smartphone-based mobile applications for scar assessment - Peter Moortgat; Jill Meirte; Mieke Anthonissen; Koen Maertens; Thibau Demarbaix; Ulrike Van Daele (Burns Open)
Scars can have a significant impact on the physical and psychosocial well-being, so the assessment of scars is crucial for accurate diagnosis, monitoring, and treatment. Traditionally, these assessments required specialized, bulky equipment that needed a wired connection to computers, making these assessment tools less accessible and efficient. The increasing omnipresence of smartphones, equipped with high-resolution cameras and advanced sensors, presents an opportunity to address this gap by developing smartphone-based assessment tools. By providing an overview of the state of smartphone-based scar evaluation tools, this paper will highlight areas for future research and development.After a comprehensive review and synthesis of existing literature on smartphone-based tools for scar assessment, the authors identified 11 devices which met the inclusion- and exclusion-criteria. Among the 11 devices, four assessed skin color, two focused on hydration, one measured elasticity, two evaluated texture, three measured temperature, and one assessed thickness. Nine devices were tested on human skin, and only two on scarred skin. Seven tools were evaluated for both validity and reliability, while four were only tested for validity. Five devices required an add-on or clip-on, while six utilized the smartphone’s built-in features. All devices demonstrated moderate to high feasibility for use in various settings and required specialized software for analysis.The development of smartphone-based tools for scar assessment represents a significant advancement, offering accessible and portable solutions for both patients and clinicians. While only two scar-specific smartphone tools currently exist, applications, such as skin hydration and color measurement show promise for future integration. These tools have proven effective in assessing general skin characteristics but require further investigation of validity and reliability in a specific scar population. Moving forward, standardized protocols and enhanced imaging technologies, such as raw image formats, will be crucial for improving reliability.